Comparative Analysis of Erythrocyte Sedimentation Rate (ESR) in Patients with P.falcifarum and P.vivax Malaria at Biak General Hospital - hidayah, Fathul; Sri Wahyuni; Samperura, Herdi; Fita Sari (Pena Medika : Jurnal Kesehatan, 2025)
P.falciparum and P.vivax infections elicit an immune response manifesting as inflammation, which is typified by alterations in various hematological parameters, including ESR. The objective of this study was to analyze the disparities in ESR values between P. falciparum and P. vivax infections. The study design employed an analytical approach, utilizing a cross-sectional study design. The population and sample consisted of 20 malaria patients at Biak General Hospital, including 9 confirmed P.falciparum infections and 11 P.vivax infections. The mean ESR values for P.falciparum infection were 32.8 mm/1 hour for males and 40.5 mm/1 hour for females. For P. vivax infection, the values were 36.4 mm/1 hour for males and 45.8 mm/1 hour for females. The ESR comparison between P. falciparum and P. vivax exhibited a significance value of 0.08>0.05, and the ESR comparison based on positivity level demonstrated a significance value of 0.253>0.05. A thorough examination of the results reveals that there is no statistically significant difference in the ESR values between P.falciparum and P.vivax infections in patients suffering from malaria.